1997
DOI: 10.1111/j.1742-1241.1997.tb11502.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hypothyroidism With Hyper‐prolactinaemia and Pituitary Enlargement Mimicking a Pituitary Macroadenoma

Abstract: SUMMARYHyperprolactinaemia can occur in patients with hypothyroidism. A 32‐year‐old woman with primary hypothyroidism presented with amenorrhoea and galactorrhoea of two years' duration. She had hyperprolactinaemia, low basal morning cortisol levels and evidence of a pituitary macroadenoma on magnetic resonance imaging. Therapy with L‐thyroxine resulted in induction of regular menses, resolution of galactorrhoea, normalisation of hormone levels and disappearance of the image of pituitary macroadenoma. It seems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…The literature search yielded 649 potentially relevant articles, spanning from January 1996 to December 2023. Following the removal of duplicates and the review of titles, abstracts, and full-length articles, we identified 55 articles [ 6 , 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ,…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded 649 potentially relevant articles, spanning from January 1996 to December 2023. Following the removal of duplicates and the review of titles, abstracts, and full-length articles, we identified 55 articles [ 6 , 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ,…”
Section: Resultsmentioning
confidence: 99%